Local Handmade / Ahmad Aiman Ahmad Tarmizi - Ahmad Tarmizi, Ahmad Aiman (2020)
The case study is important to evaluate the company’s background, company’s analysis as well as the company’s problems and alternatives that the management has provided. The methods that used to study the analysis is face-to-face interviews with the management of the company through phone calls and review from people who already have purchasedt and taste the products. SWOT analysis is vital in order to help the business to keep improving the business performance because it evaluate business wholly and points out the company’s advantages and what is lacking comparing to other businesses. Through the identification of SWOT,the company are able to revise their business plan by carrying out various of strategy. LOCAL HANDMADEproductare business that made up of accessories such as handbags, pouches, wallets and more.The business make up the competition by making their service at a more affordable price for all the community.The company also promote their business and service through advertisement in the Social Media such as Facebook where they updates any discounts and promotion to their customers.